The challenge of poverty in Malawi and Bonhoeffer's soteriology - M. Phiri (Acta Theologica)
The article explores the state, causes and effects of poverty in Malawi. It proceeds to investigate soteriology as a prominent theme in Dietrich Bonhoeffer’s theological thought. Then an exploration is made regarding how Bonhoeffer’s notion of salvation could be employed as paradigm to address the challenge of poverty in Malawi. The soteriological perspective is preferred, among many other approaches, on two-fold grounds: the hamartiological origins of poverty require a soteriological exploration and salvation is a prominent theme in Malawi. Approaching the social evils from the perspective of the doctrine of salvation could produce enduring effects. The observation is that such an approach could be more promising and could bear enduring fruits regarding addressing the challenge of poverty in Malawi.